Evaluation of drug use in stroke patients at the inpatient unit of Brebes Hospital, Central Java - Budiyanti, Nur Aini; Hapsari, Indri; Nurhidayati, Friska Suci (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Effective stroke treatment is complicated by factors such as polypharmacy, drug interactions, and side effects, leading to drug-related problems (DRPs) that hinder therapeutic outcomes. Evaluating drug use in stroke patients is crucial to ensure rational, safe, effective, and efficient treatment, ultimately improving therapeutic outcomes. Objective: This study aimed to evaluate the drug use patterns in inpatient stroke patients at Brebes Hospital, focusing on the appropriateness of drug selection, dosage, administration, and the impact of patient characteristics on DRPs. Method: A retrospective, descriptive evaluative design was employed, with data collected from medical records of stroke patients hospitalized at Brebes Hospital between May and July 2022. A total of 135 patients (110 ischemic, 25 hemorrhagic stroke) were included through consecutive sampling. Univariate analysis was used to describe patient characteristics and treatment patterns, while bivariate analysis with the chi-square test assessed the relationship between patient characteristics and DRPs. Results: The most common medications included citicoline (88.15%), clopidogrel (68.85%), and amlodipine (40.48%). DRPs were identified, including non-compliance with guidelines (1 case), contraindicated drugs (5 cases), and inappropriate drug selection (1 case). Notably, five cases of contraindicated use of omeprazole with clopidogrel and one case of phenytoin without indication were observed. Patient characteristics such as age and comorbidities did not significantly influence the incidence of DRPs (p > 0.05). Conclusion: The study found irrational drug use in stroke patients, with DRPs posing challenges for treatment optimization. Addressing DRPs through improved prescribing practices and pharmacist intervention is crucial to enhancing therapeutic outcomes in stroke management.